PRESIDEN DAN PEMBERHENTIAN HAKIM KONSTITUSI: PEMISAHAN KEKUASAAN TANPA CHECKS AND BALANCES - Kurnia, Titon Slamet (Veritas et Justitia, 2024)
On September 29, 2022, the People’s Representative Council (DPR) controversially removed Justice Aswanto and proposed Guntur Hamzah as his successor. Following the DPR’s decision, the President issued Presidential Decision Number 114/P of 2022. This process aligns with Article 24C paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which states: “The Constitutional Court is comprised of nine Justices who are appointed by the President, of whom three are proposed by the Supreme Court, three by the People’s Representative Council, and three by the President.” This provision includes two clauses: the proposal clause and the appointment clause. This article discusses the President's role in implementing the appointment clause in the case of Justice Aswanto’s removal. Using a conceptual approach, it focuses on interpreting Article 24C paragraph (3) to understand that the President's role in the appointment clause embodies the principle of checks and balances. This article argues against the President’s legalistic position of implementing the appointment clause without scrutinizing the DPR’s decision. While the appointment clause does not explicitly authorize the President to refuse issuing the Presidential Decision, this norm may be inferred from our commitment to the supremacy of the constitution.